Stres peran dan kinerja karyawan: pengujian model hubungan inverted-U - Hendryadi Hendryadi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
The purpose of this study is to examine the impact of role stress (role overload, role ambiguity, and role conflict) on the frontline employees' performance. The study employs a direct survey through a self-administered questionnaire handed out to 132 employees in the restaurant business in Jakarta, Indonesia. Hierarchical Regression Analysis is used to test the hypotheses. The finding of the study shows that the role conflict and role ambiguity affects negatively to the performance, while role overload has a positive effect. Locus of control is proven to moderate the relationship between role overload-performance and role-ambiguity-performance, but not for role conflict - performance. Implications for managers are important to reduce the role conflict and role ambiguity in the workplace to maximize employee performance.